2022
DOI: 10.3389/fnut.2022.952588
|View full text |Cite
|
Sign up to set email alerts
|

The hypolipidemic mechanism of chrysanthemum flavonoids and its main components, luteolin and luteoloside, based on the gene expression profile

Abstract: In this study, the following four groups of mice with hyperlipidemia were involved: the model control group (MC), the Chrysanthemum flavonoids group (CF), the luteolin group, and the luteoloside group. The whole gene expression profile was detected in the liver tissues of each group. Differential genes significantly enriched in the biological process of gene ontology (GO) items and Kyoto Encyclopedia of Genes and Genomes (KEGG) were selected, and 4 differential genes related to lipid metabolism were selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…According to the analysis results of the extract components and the related research on chrysanthemum flavonoids reported earlier [ 29 , 30 ], five flavonoids were selected for quantitative determination in this study. As can be seen from Figure S2 , all of the analytes showed symmetrical peak shapes, the baseline separation was obtained and the retention time and peak shapes for all of the analytes showed good correlation between the standard solution and the real sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the analysis results of the extract components and the related research on chrysanthemum flavonoids reported earlier [ 29 , 30 ], five flavonoids were selected for quantitative determination in this study. As can be seen from Figure S2 , all of the analytes showed symmetrical peak shapes, the baseline separation was obtained and the retention time and peak shapes for all of the analytes showed good correlation between the standard solution and the real sample.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found that the content of flavonoids in IC extract is relatively high. Combined with the group’s previous research on the effect of chrysanthemum flavonoids on lowering blood lipids [ 30 ], it is of practical significance to further explore the effect components of IC flavonoids on lowering blood lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Modern basic research has shown that naringin regulates lipid metabolism disorders by affecting glucose uptake and cholesterol metabolism [34]. Luteolin has significant hypolipidemic and anti-hepatic steatosis effects, and the hypolipidemic mechanism is complex and involves various biological processes, such as cholesterol, fatty acid metabolism, and glycolysis pathways [35]. Studies have suggested that apigenin may improve lipid metabolism by activating the AMPK-SREBP pathway in HepG2 cells, thereby preventing hyperlipidemia and reducing lipid accumulation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Chrysanthemum tea is a valuable flower crop in China, and it is widely used in traditional Chinese medicine for its high medicinal value [1]. It has many beneficial chemical components, including flavonoids, polysaccharides, and unsaturated fatty acids [2], as well as luteolin and luteoloside [3]. It has been proven that chrysanthemum tea can be used to fight cancer, inflammation, and obesity, protect the liver and kidneys, and guard against liver-fire hyperactivity syndrome [4].…”
Section: Introductionmentioning
confidence: 99%